Structural Integrity and Integrity Management - S. P. , Narayanan (2013)
Load Resistance Factor Design is more rational method which utilizes advanced probability theory and reliability method compared to the Working Stress Design Method. The load and resistance factors to be used in LRFD design are region specific and are obtained by calibration. In Malaysia, platforms were designed using WSD and a need was felt to introduce the rational LRFD method for which ISO 19902 was chosen as the design code. The calibration of load and resistance factors for design of platforms was presented and the results discussed. Malaysia has approximately 200 fixed offshore structures, some of which are over 40 years old, well beyond its design life. For these ageing structures to continue in service, their current structural integrity needs to be identified, addressed, prioritized and appropriate mitigation measures should be implemented. The aim of the research was to modify and develop the framework for Structural Integrity Management developed by AMOCO for carrying out risk based assessment of Malaysia’s fixed offshore platforms. This required actual fixed offshore structure data, which comprises of design, assessment and inspection records. Two important components of this framework are 1) Base line Risk ranking of Malaysia’s platforms and 2) Development of a Risk Based Underwater Inspection programme. The classification of platforms showed that many of the structures have exceeded the design life of 30 years. The baseline risk evaluation showed that 55 platforms were at “very high risk”. A risk based underwater inspection guideline was also developed. A case study performed illustrated how it affects inspection planning of platforms.